Editorial report on ISEE National Seminar 2021 - IJEE, Editors (Indian Journal of Extension Education, 2025)
Indian Society of Extension Education National Seminar 2021 on â€œTransforming Indian Agriculture through Pluralistic & Innovative Extension Approaches for Self-reliant Indiaâ€Â held at Banaras Hindu University, Varanasi, Uttar Pradesh, India during 4-6 October, 2021